Pengaruh Model Pembelajaran Conceptual Understanding Procedures Terhadap Penguasaan Konsep Fisika Ditinjau Dari Sikap Ilmiah Peserta Didik Kelas X - Ni Putu Ayu Suryani; Susilawati Susilawati; Kosim Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
Research aimed to find the effect of Conceptual Understanding Procedures learning model on the mastery of physics concepts observed from the scientific attitude of 10th-grade students. Type of research was quasi-experiment with 2x2 factorial design. Population was 10th grade students of MIA in SMAN 1 Gunungsari academic year 2017/2018, and the sampling technique was cluster random sampling. The data of the studentsÃ¢â¬â¢ mastery of concepts were collected by giving essays and the scientific attitude was measured by using questionnaires. The collected data were analyzed by applying 2-way ANOVA, assisted by SPSS 16 with (ÃÂ±) significance level of 5%. The results show that significant value for the effect of learning model consider from scientific attitude in amount 0,01 which its was smaller from (ÃÂ±), and significant value for interaction between Conceptual Understanding Procedures learning model with scientific attitude in amount 0,18 which its value is bigger from (ÃÂ±). According to data, can be conclude: there was an effect of Conceptual Understanding Procedures learning model to the mastery of physics concept in terms of scientific attitude from 10th grade studentÃ¢â¬â¢; and there was no interaction between Conceptual Understanding Procedures learning model to scientific attitude to the mastery of physics concept from 10th grade studentÃ¢â¬â¢.ÃÂ